Pengaruh Current Ratio dan Return On Equity terhadap Dividend Payout Ratio (Studi Kasus Pada Perusahaan yang Konsisten terdaftar dalam Indeks Saham LQ45 Periode 2019 – 2023) - Andini, Mellynia Tari; Maulana, M. Kausar (Jurnal Ekonomi dan Industri, 2026)
This study aims to determine Current Ratio and Return on Equity simultaneously and partially affect the Dividend Payout Ratio on companies that consistently listed in LQ45 stock index in the 2019 – 2023 period. This study uses annual financial report data. The type of data used is quantitative and obtained secondary data taken from www.idx.co.id. The sample in this study was obtained using purposive sampling, resulting 16 company samples from 26 company populations. The analysis method used is multiple linear regression analysis and data processing using SPSS 23 for windows. The results of this study indicate that simultaneously, Current Ratio and Return on Equity have a positive and significant effect on Dividend Payout Ratio. Partially, Current Ratio has negative and insignificant effect on Dividend Payout Ratio while Return on Equity has positive and significant effect on Dividend Payout Ratio.